Association of frailty with health service use among older Chinese adults: analysis of population-based panel data - Yan, Rui; Li, Lifeng; Duan, Xiaoran; Zhao, Jie (Frontiers in Public Health, 2023)
Background: Frailty is a common syndrome characterised by rapid growth in the ageing population that has an impact on healthcare systems. This study aimed to investigate the impact of frailty on health service use, and whether this effect varies with chronic diseases and socioeconomic status among older individuals in China. Methods: Balanced panel data analysis was conducted on 3306 older individuals who completed follow-ups for the three waves of the China Health and Retirement Longitudinal Study (CHARLS) in 2011, 2013, and 2015. The Physical Frailty Phenotype (PFP) Scale was used to assess frailty status. Negative binomial regression was used to test the associations between frailty status, outpatient visits in the past 4 weeks, and annual inpatient hospital days. Results: Compared with robust individuals, individuals with pre-frail or frail status were likely to report a higher number of outpatient visits (pre-frail: incidence rate ratio [IRR]=1.28, 95% CI=1.16-1.41; frail: IRR=1.45, 95% CI=1.23-1.71) and inpatient hospital days (pre-frail: IRR=1.40, 95% CI=1.24-1.58; frail: IRR=2.17, 95% CI=1.81-2.60) after controlling for all covariates. All five frailty components (weight loss, exhaustion, low physical activity, slowness, and weakness) were associated with a higher number of inpatient hospital days, and two components (weight loss and exhaustion) were associated with a higher number of outpatient visits. The effect of frailty on inpatient hospital stay persisted in different socioeconomic groups across all health insurance programmes and physical comorbidities. Conclusion: Frailty is associated with greater health service use among older individuals. Effective screening, prevention, intervention, and management of frailty may be important to reduce health service use.